2014
DOI: 10.1080/01652176.2014.966173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immune response in Shitou geese (Anser anser domesticus) following immunization with GPV-VP1 DNA-based and live attenuated vaccines

Abstract: This study showed that it is possible to induce both cellular and humoral response using DNA-based vaccines and that the pcDNA-GPV-VP1 DNA gene vaccine induced better cellular and humoral immunity than live attenuated vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…found that IFN-γ and IL-4 significantly enhanced specific Th1 and Th2 cell immune responses, respectively ( 33 ). All the above evidence suggests that AMH-INH-RFRP DNA vaccine can induce both humoral and cellular immune response through nasal immunization in buffalo, which is consistent with the previous studies on GPV-VP1 DNA vaccine ( 34 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…found that IFN-γ and IL-4 significantly enhanced specific Th1 and Th2 cell immune responses, respectively ( 33 ). All the above evidence suggests that AMH-INH-RFRP DNA vaccine can induce both humoral and cellular immune response through nasal immunization in buffalo, which is consistent with the previous studies on GPV-VP1 DNA vaccine ( 34 ).…”
Section: Discussionsupporting
confidence: 91%
“…All the above evidence suggests that AMH-INH-RFRP DNA vaccine can induce both humoral and cellular immune response through nasal immunization in buffalo, which is consistent with the previous studies on GPV-VP1 DNA vaccine (34).…”
Section: A B D E Csupporting
confidence: 91%
“…However, little is known about cellular immunity against GPV. The pcDNA-GPV-VP1 DNA vaccine was shown to induce both cellular and humoral responses, and it can induce higher cellular and humoral immunity than live attenuated vaccine (Deng et al, 2014). The codon-optimized VP2 (optVP2) is capable of forming VLPs, which are highly immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…With an average weight of 8–13 kg at 70–90 days of age, STE are one of the largest goose breeds in the world. WZE are among the smallest goose breeds in the world, normally weighing 2–3 kg at 70–90 days of age [ 1 ]. Although the two goose breeds living in Guangdong province have similar growth cycles, their growth performance, as measured by growth rate and body weight, is quite different.…”
Section: Introductionmentioning
confidence: 99%